Patent landscape of nanotechnology – based nucleic acid delivery systems for breast cancer therapies - Silva, Milca de Jesus; Saraiva Hodel, Katharine Valéria; Fonseca, Larissa dos Santos Moraes; da Hora, Helena Souza; Murari, Thiago Barros; Pinto, Claudio Damasceno; Machado, Bruna Aparecida Souza (Frontiers in Oncology, 2026)
BackgroundBreast cancer is the most prevalent malignancy among women worldwide and remains a major public health concern. Conventional treatments are often limited by adverse effects and resistance. Nucleic acid-based gene therapies, supported by nanoparticle delivery systems, offer target and efficient therapeutic alternatives. The growing number of related patents about nanotechnology-based nucleic acid delivery systems for breast cancer treatment highlights the importance of understanding this landscape to advance research and innovation. Therefore, this study aimed to analyze the global patent landscape related to nanotechnology-based delivery systems for nucleic acid therapies in breast cancer, highlighting key technological platforms, emerging trends, and opportunities for research and development.MethodologyA patent landscape analysis was conducted using the Derwent World Patents Index (DWPI, Clarivate Analytics). The search strategy combined keywords and International Patent Classification (IPC) codes related to breast cancer, nucleic acid therapies, and delivery platforms. A total of 1,084 patent families were identified. Filters were applied to classify documents as alive, dead, or indeterminate, focusing on active patents from the past five years (2020–2025), resulting in 323 patents selected for details examination.ResultsThe analysis revealed a substantial increase in patent filings over the past decade, with the United States, China, and Europe leading technological innovations. Lipid-based nanoparticles and polymeric carriers were the most frequently cited platforms. The patents showed a strong focus on targeted delivery strategies, combinatorial approaches, and RNA interference technologies.DiscussionThe findings highlight the transformative potential of nanotechnology for nucleic acid therapies in breast cancer. Despite manufacturing and regulatory challenges, the patent landscape demonstrates a dynamic and competitive field. Mapping technological developments provides valuable insights to guide strategic decisions in research and development and to identify underexplored areas with high innovation potential.